Anthony Angelo and Law Reform in Mauritius - Richardson, Ivor LM (Victoria University of Wellington Law Review, 2021)
The author, former Professor and Dean of Law at Victoria University of Wellington and President of the Court of Appeal, discusses his experience working a law reform project in Mauritius with Professor Tony Angelo. As the author has experience in income tax reform, the article focuses on Professor Angelo's legislative drafting and policy development in relation to income tax law. Professor Angelo is described as a "one man Law Reform Commission" regarding his role in Mauritius, and discusses the importance of rules relating to technical interpretation and accessibility.